Pathomorphological changes in the structure of intervertebral disc after seven and fourteen days of experimental opioid use - M. V. Pankiv; Y. V. Paltov (Kazimierz Wielki University, 2020)
We aimed to study the pathomorphological changes in the structure of intervertebral disc in the early stages of the experimental opioid use. This goal was achieved by the use of histological visualization of the intervertebral disc's structures. Histological specimens were prepared according to the typical methods using such  specimens as hematoxylin, eosin, azan and due to Heidenhain method, McManus PAS-reaction and Steedman alcian blue method. The results of this study will let form a pathomorphological basis that could be used for comparative characterization of the growth dynamics of pathomorphological changes in the intervertebral disc's structures in the early stages and compare these changes to pathomorphological signs in the late stages of experimental opioid use. These findings will provide an opportunity to establish the most appropriate time limits when these pathomorphological changes in the structure of the intervertebral disc develop and to observe the dynamics of these changes in the long term experimental opioid use.